The Problem of the Gig Economy Concept and the Solution of Islamization - Farid Khairi (Penerbit Hellow Pustaka, 2025)
This study aims to explore the integration of Islamic values into the gig economy, which has grown rapidly during the pandemic and faces challenges related to social protection and worker exploitation. The method used is qualitative, with a descriptive approach involving an analysis of the phenomena experienced by gig workers. The study was conducted in three steps: Dewesternization to identify secular elements in gig economy practices; Integration to infuse Islamic values such as justice and responsibility into the system; and Islamization to offer concrete modifications to create a more just and sustainable system. The findings suggest that the application of Islamic principles can address existing challenges, such as inequities in profit distribution and inadequate protection for workers. By adopting values such as social solidarity and environmental responsibility, the gig economy can transform into an economic mechanism that not only benefits individuals but also considers the welfare of society as a whole. This study emphasizes the importance of reforms in policies and practices to ensure that the gig economy operates in accordance with Islamic values, thereby creating a more just and sustainable economic ecosystem.